2017
DOI: 10.1002/brb3.873
|View full text |Cite
|
Sign up to set email alerts
|

Immediate and late outcomes of stenting for severe extracranial internal carotid artery stenosis in octogenarian patients

Abstract: BackgroundMultiple studies suggest that internal carotid artery stenting can be performed safely in octogenarians with low periprocedural complication rates. However, great concern still exists as to whether these patients will gain long‐term benefits from this procedure given their advanced age and uncertain life expectancy. We decided to conduct a retrospective study to determine short‐and long‐term clinical outcomes and to analyze survival duration in this population.Methods and ResultsSixty‐nine consecutiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
(40 reference statements)
0
2
0
Order By: Relevance
“…Further pooling various separate anatomic features into informal risk categories demonstrate significant association of 'high risk' anatomy with age over 80 years [12]. Although there appears to be increased risk of AIS in elderly patients undergoing CAS [78], univariate analysis of complication rates between anatomic risk categories while stratifying elderly (over 80 years of age) and younger patients undergoing CAS [79], making it difficult to define a causal relationship regarding arch variations. Illustratively, univariate studies regarding populations separated by age found no association with perioperative morbidity [79,80].…”
Section: Patient Agementioning
confidence: 99%
See 1 more Smart Citation
“…Further pooling various separate anatomic features into informal risk categories demonstrate significant association of 'high risk' anatomy with age over 80 years [12]. Although there appears to be increased risk of AIS in elderly patients undergoing CAS [78], univariate analysis of complication rates between anatomic risk categories while stratifying elderly (over 80 years of age) and younger patients undergoing CAS [79], making it difficult to define a causal relationship regarding arch variations. Illustratively, univariate studies regarding populations separated by age found no association with perioperative morbidity [79,80].…”
Section: Patient Agementioning
confidence: 99%
“…Particular care must be taken in older populations in which prevalence of high-risk factors is increased. Appropriate patient selection and procedural planning has been demonstrated to allow for effective and safe treatment may be achieved in high-risk populations [78].…”
Section: Anatomic Guidelines For Endovascular Extracranial Carotid Interventionmentioning
confidence: 99%